Providing Evidence and "Voice" During the COVID-19 Pandemic Using Online Rapid Response Surveys: Lessons from the UJ/HSRC COVID-19 Democracy Survey. Issue 3 (1st October 2020) - Runciman, Carin; Rule, Stephen; Bekker, Martin; Roberts, Benjamin; Orkin, Mark; Davids, Yul Derek; Bohler-Muller, Narnia; Alexander, Kate
ABSTRACT: COVID-19 presents significant challenges to society and to social scientists in their attempts to understand the unfolding consequences of the pandemic. This article examines how the UJ/HSRC COVID-19 Democracy survey responded to these challenges by conducting a series of rapid-response non-probabilistic surveys using a mass membership online data-free platform, known as the Moya messenger app. While not without its limitations, we argue that the narrowing "digital divide" in South Africa means that online survey research is of increasing utility to researchers under the conditions of the pandemic and beyond. By offering insight into the technicalities of designing, translating and fielding the survey we aim to share insights into best practice that can further develop online survey research in South Africa. In particular, we reflect upon why the river sampling offered by the Moya messenger app was favoured over online panel data. This leads into a discussion of the process of weighting the data to replicate the national population, and the potential biases among participants versus non-participants in the surveys. The article then moves on to illustrate how the findings were used to provide evidence to policymakers and "voice" to adults living in South Africa about their experiences of the pandemic and their views on policy responses. The article considers how the research contributed to the public discourse around the pandemic response in 2020, including the public's views on various pandemic policy decisions, school closures and pandemic fatigue.